Risk Management in Banking:The Tendency of Risk Management Development and Changes in Financial Crisis. - Zhang, Lan (2011)
As the market instability and uncertainty that economic and business environment become more complex than any time before. In real condition, there are significant financial volatility and distress that exist in financial institutions, particularly in those with large debt and commodity price exposures. Therefore risk management in recent decade has been largely required and improved to financial sectors. In this paper, we conduct content analysis through annual reports of four leading banks in UK to disclose the development tendency of risk management in UK and to identify the changes and effect in risk management before or after financial crisis. Meanwhile, it will introduce the various risks faced by banks and the definition of financial crisis and bank crisis. In times of such turbulence financial environment, hope this research will reveal some identical information in banking risk management.